PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL TREFFINGER BERBANTUAN APLIKASI GEOGEBRA PADA MATERI BANGUN RUANG SISI DATAR DI KELAS VIII SMP - Syarul Ramadhan; Alzaber Alzaber; Agus Dahlia; Rahma Qudsi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to produce valid mathematics learning tools. The development of the device in this study uses the Plomp development model which is divided into 5 phases, namely initial investigation, design, relation/construction, test, evaluation and revision and implementation. The data collection instruments used were in the form of RPP validation sheets and LKPD validation sheets. Data collection techniques were carried out by collecting validation questionnaires that had been filled out by experts. The data analysis technique used is validation data analysis. The results of the analysis of device validation data on the data obtained from the three validators obtained an average RPP validation score of 81.6% which is included in the fairly valid category which can be used but needs minor revisions. The average score of LKPD validation is 78.67% which is included in the fairly valid category that can be used with minor revisions. Furthermore, the RPP and LKPD were revised according to the validator's suggestion so that a mathematics learning device with the Treffinger model with the help of the Geogebra application was produced on valid flat-sided geometry material, which the device was feasible and could be used in the learning process.